(untitled) (LIS TODAY, 2025)
The Online Directory of CSU Ph. D. Awarded Thesis Portal is developed to address the lack of a centralized mechanism for accessing thesis-related information at Central Sanskrit University (CSU). Prior to this initiative, research scholars faced many challenges in locating thesis topics, supervisors, subjects, year and the availability of physical copies due to the absence of a searchable database. Existing resources, such as non-searchable PDF lists of theses awarded from 2018 onward, were inadequate, leaving earlier data inaccessible to the research scholars. This research highpoints the implementation of a dynamic web-based search portal designed to provide real-time access to a comprehensive thesis database. The portal integrates HTML and SQL-based technologies to facilitate efficient retrieval of information such as thesis titles, authors, supervisors, and campus locations of physical copies. Key features include user-friendly search functionality, advanced filtering options, and automated database updates to ensure accuracy and accessibility. The results demonstrate that the portal significantly enhances usability, reduces inefficiencies, and supports scholars in identifying research gaps and opportunities for further study. By bridging the accessibility gap and modernizing thesis data management across CSU’s 12 campuses, the portal sets a new standard for resource availability in academic institutions. This initiative underscores the importance of leveraging digital tools to advance research and improve academic support systems.